2004
DOI: 10.1124/jpet.104.071464
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy with Adenoviral Plasmids or Naked DNA of Vascular Endothelial Growth Factor and Platelet-Derived Growth Factor Accelerates Healing of Duodenal Ulcer in Rats

Abstract: After we demonstrated that daily intragastric administration of angiogenic growth factors like basic fibroblast growth factor (bFGF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…These studies clearly proved that the local gene therapy with plasmid cDNA encoding VEGF significantly increases angiogenesis and accelerates gastric esophageal ulcer healing (51,52). Szabo and co-workers successfully applied gene therapy with adenoviral plasmids or naked DNA of VEGF and PDGF to duodenal ulcers and demonstrated that this treatment accelerates duodenal ulcer healing (53,54).…”
Section: Gene Therapy For Ulcer Healingmentioning
confidence: 89%
“…These studies clearly proved that the local gene therapy with plasmid cDNA encoding VEGF significantly increases angiogenesis and accelerates gastric esophageal ulcer healing (51,52). Szabo and co-workers successfully applied gene therapy with adenoviral plasmids or naked DNA of VEGF and PDGF to duodenal ulcers and demonstrated that this treatment accelerates duodenal ulcer healing (53,54).…”
Section: Gene Therapy For Ulcer Healingmentioning
confidence: 89%
“…This process involves many genes encoding growth factors, including epidermal growth factor, VEGF, keratinocyte growth factor, hepatocyte growth factor, platelet-derived growth factor, basic fibroblast growth factor, and angiopoietins. It has been reported that genes encoding these growth factors have an ulcer healing effect in vivo [2,[32][33][34]. Moreover, gene therapy has been tried for gastric cancer in vitro and in vivo with various therapeutic genes, namely p53 [35], FHIT [36], NK4 [37,38] and the Fas ligand [39].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that genes encoding these growth factors have an ulcer healing effect in vivo. 2,[36][37][38] Moreover, gene therapy has been tried for gastric cancer in vitro and in vivo with various strategies, such as transfer of suicide genes, 39) the p51A gene, 40) dominant negative insulin-like growth factor I receptor gene, 41) and RhoA and RhoC short interfering RNA. 42) Efficient and targetselective gene delivery systems are important factors determining whether or not gene therapy succeeds.…”
Section: Discussionmentioning
confidence: 99%